External and internal influences on mobile phone use while driving: Combining the theories of deterrence and self-determination. (February 2023) - Truelove, Verity; Watson-Brown, Natalie; Oviedo-Trespalacios, Oscar
Highlights: Changes to legal sanctions did not significantly deter phone use while driving. Self-regulation, though the lens of self-determination theory, predicted behaviour. Phone use while driving requires countermeasures that focus on a whole system. Police enforcement should be part of a multi-faceted road safety intervention. Abstract: Objectives: Various legal countermeasures have been introduced in numerous jurisdictions worldwide to reduce the risky behaviour of phone use while driving. However, external factors do not influence behaviour alone; internal factors may also play a large role in influencing behaviour. Therefore, the aim of this study was to examine the impact of both external and internal influences on hand-held phone use while driving. Methods and analysis: The influence of external factors was examined after a higher penalty and a trial for mobile phone detection cameras was introduced in Queensland, Australia, utilising deterrence-theory related constructs. Meanwhile, internal factors were examined through the lens of self-determination theory to determine the relevance of self-regulation to phone use while driving, over and above the effect of deterrence factors. Findings: A total of 866 participants (M age = 37.51 years, SD = 17.23) completed a survey examining these variables. Despite the changes to the penalty and enforcement, the legal factors did not significantly deter drivers from phone use while driving. Instead, participants reported avoiding punishment, which influenced further engagement in the behaviour. Meanwhile, indicators of self-regulation including effort/importance, perceived pressure, and relatedness were found to have a more salient impact on the behaviour, whereby drivers who reported high levels of internalised regulatory processes were less likely to use a hand-held phone while driving. Novelty and improvement: These results provide a novel contribution to understanding road rule compliance and have important implications for both theory and practice. For example, it can be suggested that legal countermeasures need to be improved, while non-legal countermeasures that target internalisation is a promising avenue for future research.